2022
DOI: 10.3389/fmicb.2022.860749
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Direct Interspecies Electron Transfer via Adding Conductive Materials in Anaerobic Digestion: Mechanisms, Performances, and Challenges

Abstract: Anaerobic digestion is an effective and sustainable technology for resource utilization of organic wastes. Recently, adding conductive materials in anaerobic digestion to promote direct interspecies electron transfer (DIET) has become a hot topic, which enhances the syntrophic conversion of various organics to methane. This review comprehensively summarizes the recent findings of DIET mechanisms with different mediating ways. Meanwhile, the influence of DIET on anaerobic digestion performance and the underlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Efficient propionate degradation in R2 improved the ACM and HTM activities. It was reported that the syntrophic degradation rates of propionate and butyrate in an anaerobic reactor could be increased by 1.5 and 4.2 times by activated carbon supplementation, respectively 14,29 . As a result, acetate and hydrogen from propionate degradation could stimulate the enrichment of acetoclastic and hydrogenotrophic methanogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient propionate degradation in R2 improved the ACM and HTM activities. It was reported that the syntrophic degradation rates of propionate and butyrate in an anaerobic reactor could be increased by 1.5 and 4.2 times by activated carbon supplementation, respectively 14,29 . As a result, acetate and hydrogen from propionate degradation could stimulate the enrichment of acetoclastic and hydrogenotrophic methanogens.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the syntrophic degradation rates of propionate and butyrate in an anaerobic reactor could be increased by 1.5 and 4.2 times by activated carbon supplementation, respectively. 14,29 As a result, acetate and hydrogen from propionate degradation could stimulate the enrichment of acetoclastic and hydrogenotrophic methanogens. Similar results were shown by other studies reporting that supplementation of activated carbon increased methane production 1.8-fold and methane yield by 17.4% higher than the control reactor due to the enrichment of specific microorganisms involved in DIET, such as Geobacter, Methanosaeta, Methanospirillum, and Methanolinea.…”
Section: Reactor Performancesmentioning
confidence: 99%
“…This archaeon also showed a positive correlation with the previously mentioned amino-acid degrading microbes, which also have active C-type cytochromes and pili synthesis ability, both of which are essential for DIET (MAG_72_3 and MAG_394_2; Suppl. Table 5) [65,[72][73][74]. During metabolic processes electrons can be generated and carried by reducing equivalents such as reduced ferredoxin.…”
Section: Ad Chemical Parameters and The Core Communitymentioning
confidence: 99%
“…BC also improves buffer capacity through the presence of functional groups, and ions such as Na + , K + , Ca 2+ , and Mg 2+ (Zhao et al, 2021). Moreover, it is considered that BC promotes direct interspecies electron transfer (DIET) between some syntrophic bacteria and methanogens (Chen et al, 2022), accelerating substrate degradation, lowering volatile fatty acids concentration, and increasing methane production. The DIET is a mechanism that bypasses a need for reduced electron carriers (formate or H 2 ) for the complex organic matter transformation into methane due to the presence of free electron flow between cells of different microorganism species by physical and electrical connections (Liu et al, 2012;Gahlot et al, 2020).…”
Section: Introductionmentioning
confidence: 99%